Documenting Outcomes of a Faculty Training Workshop on Problem-Based Learning - Moriearty,Pamela L. (1999)
Abstract: A faculty training workshop on problem-based learning (PBL) methods was provided to educators at a public medical school in Brazil. Wprkshop activities were designed to address specific knowledge, skill and attitudinal objectives that had been defined beforehand. Participants completed a structured questionnaire before and after the workshop to document attainment of the objectives. Twelve participants completed the 20-hour workshop, and questionnaire results. Though there were certain limitations on interpretation of the pre/post questionnaire, it does provide some assurance to program organizers and sponsors that objectives are attained. Participants' responses also help organizers improve their delivery techniques.